Selection of filtering agent and filter cloth to separate cells of probiotic yeast using a monophasic filter system - Castillo Saldarriaga, Carlos; Gómez Álvarez, Martha Isabel (‎‎Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2019)
The efficiency of separation operations is a critical point to determinate the yield and economic viability of a production process. Because of this, the selection of adequate operation parameters has become an important part in the design of a new bioprocess. [1, 2]. Due to its low cost and easily transformation to industrial scale, the cross-flow filtration had been highly studied in terms of process performances of microorganism biomass separation without being concerned about their viability. In this work, two parameters of cross-flow filtration were evaluated to separate yeast cells from fermented broth. Meyerozyma guilliermondii was the reference biology system used in the experiments [3]. First, an evaluation of the compatibility of two filtering agents over yeast cells was conducted. After the filtering agent was selected, the efficiency of separation was determined over different filter cloth on a monophasic filter system.